Manajemen Logistik Non Medis Di Rumah Sakit Umum Daerah Salewangan Maros - Rahmatullah, Madani; Mahsyar, Abdul; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to discuss the implementation of non-medical logistics management at the Salewangan Maros General Hospital which discussed the planning function, procurement function, care function and rescue function. This study  used qualitative research with the type descriptive research that did not test certain hypotheses. It  was to find out the logistics management. The results showed that planning function indicators were categorized as good because they were structured. Logistics goods procurement, the implementation of the procurement function had not been well categorized, according to the nature of the procurement was already using direct procurement. Then in the goods maintenance function was effective but did not damage goods that were not suitable for use, the change depends on the procurement process itself. The implementation of the appointment function indicator could not be categorized as good or bad this year, but there had not been a removal of goods.